A Method of Images to Study Plate-Impact-Induced Cavitation in Aluminum through Molecular Dynamics Simulation - Yingzhen Jiang; Ziyang Ma; Haijian Chu; Huiling Duan (Metals)
The tensile stress generated by the superposition of two reflection waves in the target plays a critical role in explaining plate-impact-induced spalling. A method of images is proposed to simulate the physical process of wave superposition and this method is applied in order to study the cavitation mechanism in single-crystal Al through molecular dynamics simulation. The critical impact-load velocity for the cavitation obtained by this method is as small as 400 m/s, which is much lower than the result (650 m/s) obtained by the conventional piston-load method. The new cavitation mechanism found is distinctively different from the conventional dislocation-entanglement-induced cavitation under high-velocity impact. The new mechanism involves two key events: firstly, a crack-like defect is formed and its relevant atomic bonds are broken under high tensile stress, resulting in a great momentum of related atoms; and secondly, previous high-momentum atoms collide with the atoms in their running way, resulting in the destruction of the original FCC structure locally and nanovoids or penny-shaped voids being formed. Additionally, the cavitation region, the number of voids, and delamination surfaces increases with the impact-load rate.